Comparison between standard and dual mobility implants in total hip arthroplasty for femoral neck fractures in elderly - S. , Deepak; B. S., Abishek; ., Hemant (International Journal of Research in Orthopaedics, 2023)
Background: Dislocation is a major concern after total hip replacement (THR) in displaced fracture neck of femur. Recent studies have shown reduced dislocation rates with dual mobility THR (DMTHR) for femur neck fractures; however, there is a lack of comparative research to show its superiority over conventional THR. Further, its role in the Asian subcontinent, where the patient requires sitting cross-legged or squatting, has not been studied. Methods: A prospective cohort study of 30 elderly patients with displaced NOF with a minimum follow-up of 2-year. Sixteen patients were operated on with DMTHR and fourteen patients with conventional THR. Both the groups were matched; radiological and functional outcomes in terms of Harris hip score (HHS), visual analog scale (VAS), range of motion, and dislocation rate were compared between the two groups. Results: Mean HHS of the DMTHR group was 79.99 at three months and 92.73 at the end of the 2 year postoperatively, which was significantly better than the conventional THR group 59.5 at three months and 88.14 at 2-year. The range of motion was significantly better in the DMTHR group than the conventional THR group. There was no significant difference in radiological outcomes and postoperative dislocation rate between the two groups. Conclusions: Dual mobility implants give better results than conventional implants for primary THA in elderly patients of displaced FNOF regarding better function and greater range of motion. More long-term multicentric studies are still needed.